DEVELOPMENT OF THE PRINCIPLE CIRCUIT OF THE PISTON RINGS SLUGS CASTING PROCESS - A. N. Krutiiin; A. I. Stanuk; D. I. Stanuk (Литьë и металлургия)
The results of execution of the principal scheme of casting process of the piston ring slugs by means of dipping are presented.